A COMPARATIVE STUDY OF THE EFFICACY AND TOLERABILITY OF ORIGINAL AND GENERIC BISOPROLOL IN MONOTHERAPY OR IN COMBINATION WITH S-AMLODIPINE AND INDAPAMIDE IN PATIENTS WITH ARTERIAL HYPERTENSION 1-2 DEGREES. RESULTS OF THE CLINICAL RANDOMIZED CROSSOVER STUDY - S. Yu. Martsevich; S. N. Tolpygina; V. P. Voronina; O. V. Lerman; Yu. V. Lukina; N. A. Dmitrieva; I. V. Vashurina (Рациональная фармакотерапия в кардиологии)
Aim. To study the clinical equivalence of original and generic drugs of bisoprolol in patients with arterial hypertension (HT) 1-2 degrees according to protocol recommended by the Society of Cardiology of the Russian Federation for comparative studies. Material and methods. 30 patients with HT 1-2 degrees were examined. Patients were randomized into group 1 (original bisoprolol 5 mg/day) or group 2 (generic bisoprolol 5 mg/day). In case of insufficient antihypertensive effect bisoprolol dose was increased or S-amlodipine and then indapamide were added. After the first treatment period (8 weeks) was completed 2-week wash-out period started and then the second period (8 weeks) of treatment (taking alternative medicine of bisoprolol) began. Blood pressure (BP), heart rate, ECG, adverse effects were recorded in patients. Results. After 8 weeks of therapy BP reduction was 27.2±12.2/12.0±6.1 mm Hg in group 1 and 29.9±10.5/12.5±7.2 mm Hg in group 2 (p<0.001 for both groups), intergroup differences were insignificant. Target BP levels were achieved in 79.3% of patients in both groups. Heart rate decrease was 11.1±12.9 in group 1 and 8.5±8.6 beats/min in group 2 (p<0.05 for both groups). Significant dynamics of PQ interval were not found in both groups. The groups were comparable in terms of treatment safety and tolerability. Conclusion. Therapeutic equivalence of original and generic bisoprolol is shown in patients with HT 1-2 degrees.